Diatom analysis of the Late Quaternary sediments from the area of the Czech Republic - Bešta, Tomáš (Jihočeská univerzita, 2014)
Diatom analysis performed on sediment profiles from several localities provided information on past changes in the aquatic environment related to climatic and artificial shifts since the Last Glacial-Interglacial Transition. The practicality of diatom analysis from fish guts of three European fish species in palaeolimnological studies was tested.
Diatom analysis of the Late Quaternary sediments from the area of the Czech Republic
Keywords: Diatoms; Palaeolimnology; Last Glacial-Interglacial Transition; Holocene; Diatoms; Palaeolimnology; Last Glacial-Interglacial Transition; Holocene